Promissory Note Accounting Training for High School Students - Yanti, Yanti; Melvin, Melvin (Transpublika Publisher, 2025)
The objective of this training program is to offer instruction in promissory note accounting to grade XII students specializing in Mathematics and Natural Sciences at SMA Kristen Yusuf. These students have not been exposed to this subject in their school curriculum. The training session took place on May 2, 2025, with a total of 21 students in attendance. The instructional methods utilized included theoretical explanations presented through modules, practice questions, facilitated discussions, and quizzes for feedback. As a result of the training, students exhibited a marked improvement in their comprehension of promissory note accounting concepts and demonstrated active engagement in the learning process. The overall outcome of the program was deemed successful in providing students with a foundational understanding of promissory note accounting principles. It is recommended that similar training sessions be conducted in the future, targeting a broader audience and extending the duration of the program for enhanced educational impact.